Proceedings of the 2nd Workshop on Computing News Storylines (CNS 2016) 2016
DOI: 10.18653/v1/w16-5705
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Identification of Narrative Diegesis and Point of View

Abstract: The style of narrative news affects how it is interpreted and received by readers. Two key stylistic characteristics of narrative text are point of view and diegesis: respectively, whether the narrative recounts events personally or impersonally, and whether the narrator is involved in the events of the story. Although central to the interpretation and reception of news, and of narratives more generally, there has been no prior work on automatically identifying these two characteristics in text. We develop aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…beings) because we are interested in extracting the information most closely coupled with people or characters. We were less concerned In the prior section we showed the PEDC contains a significant amount of personal events by running the POV and diegesis extractors from Eisenberg and Finlayson (2016). We found that the PEDC contains 56% first-person narrators, and 32% homodiegetic narrators.…”
Section: What Are Personal Events?mentioning
confidence: 85%
See 2 more Smart Citations
“…beings) because we are interested in extracting the information most closely coupled with people or characters. We were less concerned In the prior section we showed the PEDC contains a significant amount of personal events by running the POV and diegesis extractors from Eisenberg and Finlayson (2016). We found that the PEDC contains 56% first-person narrators, and 32% homodiegetic narrators.…”
Section: What Are Personal Events?mentioning
confidence: 85%
“…We back our claim (that dialogue is different than newswire) by comparing the distributions of narrative point of view (POV) and diegesis of the narrators in PEDC with the Reuters-21578 newswire corpus. 2 Eisenberg and Finlayson (2016) found that narrators in newswire texts from the Reuters-21,578 corpus use the first-person POV less than 1% of the time, and are homodiegetic less than 1% of the time. However, in the 14 episodes (1,028 utterances) of This American Life, we found that 56% narrators were first-person, and 32% narrators were homodiegetic.…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…An annotation scheme, NarrativeML, was developed to facilitate the annotation of these concepts. More recently, Eisenberg and Finlayson (2016) trained SVM models to distinguish between first-person and third-person point of view in a narrative, as well as for determining whether the narrator is involved in the story, i.e. diegesis.…”
Section: Related Workmentioning
confidence: 99%
“…This chapter was adapted from an article I published in the Proceedings of the Second Workshop on Computing News Storylines(Eisenberg, November 2016).…”
mentioning
confidence: 99%